Reviews (Blackfriars, 1935)
HISTORY AND BIOGRAPHY: the Emperor Charles IV. By Bede Jarrett, O.P., M.A. HISTORY AND BIOGRAPHY: Newman en zijn‘Idea of a University.’ By Paul Sobry. MISCELLANEOUS: Problems of Mind and Matter. By John Wisdom. MISCELLANEOUS: De Historia Canonis Utriusque Testamenti. By P. Seraphinus M. Zarb, O.P. MISCELLANEOUS: The Old Testament in the Light of Anthropology. By E. O. James. MISCELLANEOUS: The Stranger. A Study in Social Relationships. By M. M. Wood. MEDIAEVAL STUDIES THE PLAY GRAMOPHONE